2004
DOI: 10.1159/000076995
|View full text |Cite
|
Sign up to set email alerts
|

The Heart in Wegener’s Granulomatosis

Abstract: Wegener’s granulomatosis (WG) is a necrotizing vasculitis that mainly affects the respiratory tract and kidneys. Of note, involvement of the heart is being increasingly recognized in these patients. Cardiac manifestations can arise from the coronary arteries, pericardium, myocardium, endocardium, valves, conduction system and great vessels, but in most cases cardiac involvement is clinically silent. Consequently, a regular cardiovascular evaluation, including echocardiography, should be performed in every pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 32 publications
1
30
0
2
Order By: Relevance
“…Cases of a mass in the left ventricle have also been reported (10), and severe manifestations include congestive cardiomyopathy (11) and pericardial tamponade (12). Furthermore, valvular/endocardial diseases that occasionally mimic left atrial myxoma or bacterial endocarditis have been reported to be manifestations of GPA (13,14), similar to that observed in the present patient. Although the mass observed in this case was not assessed histologically, we assumed the presence of inflammatory cell infiltration with or without granulomas or myxomatous degeneration (13).…”
Section: Discussionsupporting
confidence: 82%
“…Cases of a mass in the left ventricle have also been reported (10), and severe manifestations include congestive cardiomyopathy (11) and pericardial tamponade (12). Furthermore, valvular/endocardial diseases that occasionally mimic left atrial myxoma or bacterial endocarditis have been reported to be manifestations of GPA (13,14), similar to that observed in the present patient. Although the mass observed in this case was not assessed histologically, we assumed the presence of inflammatory cell infiltration with or without granulomas or myxomatous degeneration (13).…”
Section: Discussionsupporting
confidence: 82%
“…Pericardial pathology has demonstrated diffuse, as well as focal, areas of involvement. Pericardial effusions and cardiac tamponade have been reported [4,7]. The endocardium (including valves), myocardium, and epicardium are also targets of the vasculitic process.…”
Section: Discussionmentioning
confidence: 99%
“…The endocardium (including valves), myocardium, and epicardium are also targets of the vasculitic process. The epicardium has shown granulomatous inflammatory foci [4,7] and the myocardium has shown granulomatous foci, perivascular inflammation and necrotizing arteriolitis. The endocardium and valves were also involved in several cases with inflammation, fibrinoid necrosis, and granulomatous formation of the mitral and, less commonly, tricuspid valves [7,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…У пациентов с системными васкулитами причиной сердечно-сосудистых симптомов может быть специфическое поражение миокарда или сосудов сердца. У больных гранулематозом Вегенера описаны случаи ИМ, связанного с некротизирующим васкулитом коронарных артерий [22,23].…”
Section: кардиосклерозunclassified